IMPLEMENTASI KURIKULUM MERDEKA BERBASIS PEMBELAJARAN MENDALAM PADA PENDIDIKAN INKLUSI DI KOTA MAKASSAR - Ramadhani Fitri, Siti Aisyah; Wahira; Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Merdeka Curriculum management in improving inclusive education at Kharisma and Pertiwi Elementary School, Makassar. This research employed a qualitative approach with a case study design. Reseach subjects included the principal, classroom teachers, and special education assistants. Data were collected through observation, in-depth interviews,and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that curriculum planning has referred to the principles of the Merdeka Curriculum but has not been fully responsive to the needs of students with special needs. The implementation of inclusive learning still faces limitations in teacher competence and supporting facilities, while learning evaluations has not optimally applied differentiated assessment. Supporting factors include the principal’s commitment and teacher motivation, while inhibiting factors include limited inclusive education training and technical support. This study recommends strengthening adaptive curriculum management and enhancing teacher capacity to support inclusive education effectively.